Employing Explainable AI to Optimize the Return Target Function of a Loan Portfolio - Gramespacher, Thomas; Posth, Jan-Alexander (Frontiers in Artificial Intelligence, 2021)
In recent years, data science methods have been developed considerably and have consequently found their way into many business processes in banking and finance. One example is the review and approval process of credit applications where they are employed with the aim to reduce rare but costly credit defaults in portfolios of loans. But there are challenges: Since defaults are rare events, it is – even with machine learning (ML) techniques – difficult to improve prediction accuracy and improvements are often marginal. Furthermore, while from an event prediction point of view a non-default is the same as a default, from an economic point of view much more relevant to the end-user, e.g. a bank, it is not due to the high asymmetry in cost. Lastly, there are regulatory constraints when it comes to the adoption of advanced ML – thus the call for explainable artificial intelligence (XAI) issued by regulatory bodies like FINMA and BaFin. In our paper, we will address these challenges. In particular, based on an exemplary use case we show how ML methods can be adapted to the specific needs of credit assessment and how, in the case of strongly asymmetric costs of wrong forecasts, it makes sense to optimise not for accuracy but for an economic target function. We showcase this for two simple and ad-hoc explainable ML algorithms, finding that in the case of credit approval, surprisingly high rejection rates contribute to maximising profit.